2013
DOI: 10.1042/cs20130442
|View full text |Cite
|
Sign up to set email alerts
|

In vivoevidence of an age-related increase in ATP cost of contraction in the plantar flexor muscles

Abstract: Impaired skeletal muscle efficiency potentially contributes to the age-related decline in exercise capacity and may explain the altered haemodynamic response to exercise in the elderly. Thus we examined whether (i) the ATP cost of contraction increases with age, and (ii) this results in altered convective O(2) delivery to maintain microvascular oxygenation in the calf muscle. To this aim, we used an integrative experimental approach combining (31)P-MRS (magnetic resonance spectroscopy), Doppler ultrasound imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 75 publications
(98 reference statements)
1
26
1
Order By: Relevance
“…This likely indicates that the isokinetic contractions were less energetically demanding than the isotonic contractions for both age groups. Thus, based on previous studies (Layec et al 2014), it seems that the greater fatigability reported here for the isotonic contractions could reflect a larger metabolic cost per contraction during the isotonic task for the older men than young.…”
Section: Task Failurementioning
confidence: 97%
See 3 more Smart Citations
“…This likely indicates that the isokinetic contractions were less energetically demanding than the isotonic contractions for both age groups. Thus, based on previous studies (Layec et al 2014), it seems that the greater fatigability reported here for the isotonic contractions could reflect a larger metabolic cost per contraction during the isotonic task for the older men than young.…”
Section: Task Failurementioning
confidence: 97%
“…However, the metabolic demand of shortening contractions is greater than that of sustained isometric contractions (Newham et al 1995), and the enhanced energetic cost likely mitigates any age-related metabolic advantage. For example, during constant load sub-maximal isotonic plantar flexions at an effort equivalent to~40 % maximal power output, Layec et al (2014) found that the ATP cost per contraction was remarkably higher for older adults than young. Moreover, this increased energy usage was correlated with age-related impairments in plantar flexor power.…”
Section: Task Failurementioning
confidence: 99%
See 2 more Smart Citations
“…In healthy muscles ATPmax correlates with mitochondrial content measured by citrate synthase activity and ex vivo respiratory capacity in human muscle[41], mitochondrial volume density by EM[42, 43], and maximal mitochondrial respiratory capacity in permeabilized fibers[44]. Multiple studies have found that ATPmax decreases in aged skeletal muscles in mice and humans and increases following exercise training[35, 36, 45], although whether the lower ATPmax is an intrinsic aspect of aging muscle or due to changes in physical activity with age remains controversial[46, 47]. Interestingly, recent work has demonstrated that under conditions of skeletal muscle dysfunction or stress the relationship between ex vivo measures of mitochondria capacity and in vivo ATPmax is not as consistent[34, 35] suggesting that a stressed cellular environment exerts another level of control over mitochondrial function that may not be reflected in ex vivo assays (discussed below).…”
Section: In Vivo Approaches For Measuring Mitochondrial Phosphorylmentioning
confidence: 99%